Strategi Diversifikasi Produk Kerupuk Kamang dalam Meningkatkan Daya Saing Pasar Lokal : Studi Kasus Usaha Ibu Rumah Tangga - Nabila Falian; Yenty Astarie Dewi (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study aims to formulate a diversification strategy for the development of Kerupuk Kamang products in order to increase competitiveness in the local market by using the Business Model Canvas (BMC) approach. The background of this research is based on the increasing competition in the local culinary industry, which requires micro-enterprises, especially home-based businesses managed by housewives, to innovate their products and improve their business models. The method used in this study is descriptive with a qualitative approach. Data were collected through observation, structured interviews, and documentation involving Kerupuk Kamang business actors in Nagari Gadut, Tilatang Kamang District, as well as consumers. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that the development of Kerupuk Kamang is still constrained by limited product variation, less attractive packaging, and dependence on retailers for marketing. The study concludes that a diversification strategy in product development based on the Business Model Canvas can serve as an effective solution to improve the competitiveness of Kerupuk Kamang in the local market. The implications of this research are expected to serve as a reference for local MSME actors in formulating sustainable product development strategies and increasing business independence.